Hornstedtia garbosa (Zingiberaceae: Alpinieae), a new species from Mindanao, Philippines - Naive, Mark Arcebal K.; Alejandro, Grecebio Jonathan D. (Phytotaxa, 2018)
Hornstedtia garbosa Naive & Alejandro, a new endemic species from southern Philippines, is here described and illustrated. This new species is comparable to H. microcheila Ridl. and H. sanhan M.F. Newman but distinct by its obovate labellum which is white with a red centre. Information on habitat and ecology as well as notes on its similarity to other probably allied species of the genus are provided. An identification key to the five recognized Philippine Hornstedtia species is also included.